2018
DOI: 10.1210/js.2017-00465
|View full text |Cite
|
Sign up to set email alerts
|

Health and Cardiometabolic Disease in Transgender Adults in the United States: Behavioral Risk Factor Surveillance System 2015

Abstract: ContextLittle is known about the health of transgender adults in the United States, a growing population. There have been no large reports examining differences in health status and cardiometabolic disease in subgroups of transgender adults [female-to-male (FTM), male-to-female (MTF), and gender nonconforming (GNC)] in the United States.ObjectiveCompare the health status and prevalence of cardiometabolic disease among specific subgroups of transgender adults (FTM, MTF, GNC) with those of cisgender adults in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
2
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 19 publications
1
52
2
2
Order By: Relevance
“…8 Overall, probability samples have found no differences in chronic conditions between transgender and cisgender individuals, except that prevalence of myocardial infarction appeared to be elevated among transgender women and gender nonconforming individuals. 6,7,18 In contrast, studies using BRFSS data have consistently reported a higher prevalence of disability and activity limitation in the transgender population than in the cisgender population [5][6][7][8] ; however, the magnitude of this disparity was less than that implied by the findings for transgender people in the USTS. 16 Notably, 41% and 40% of transgender respondents in the NTDS and USTS, respectively, reported at least one lifetime suicide attempt.…”
Section: Sociodemographicsmentioning
confidence: 73%
“…8 Overall, probability samples have found no differences in chronic conditions between transgender and cisgender individuals, except that prevalence of myocardial infarction appeared to be elevated among transgender women and gender nonconforming individuals. 6,7,18 In contrast, studies using BRFSS data have consistently reported a higher prevalence of disability and activity limitation in the transgender population than in the cisgender population [5][6][7][8] ; however, the magnitude of this disparity was less than that implied by the findings for transgender people in the USTS. 16 Notably, 41% and 40% of transgender respondents in the NTDS and USTS, respectively, reported at least one lifetime suicide attempt.…”
Section: Sociodemographicsmentioning
confidence: 73%
“…However, it is known that not all hypertensive patients have equal chances for disease progression [2]. e factors of cardiometabolic risk are the most thoroughly investigated: a number of systemic publications are devoted to study of the prognosis of these factors for patients with cardiovascular diseases in developed countries [3]. At the same time, there are often studies in which autonomic regulation and parameters of hemodynamic were studied resulting in inclusion of respective indicators in the management for sudden death issued by the American Heart Association [4].…”
Section: Introductionmentioning
confidence: 99%
“…Of particular concern were participants' reports of hypertension and high cholesterol, which they attributed to stress and inadequate nutrition arising from food insecurity. Recent population-based studies indicate that gender nonconforming, transgender females, 45 and transgender males 46 exhibited disparities in cardiovascular disease. While larger studies are needed, it may be that food insecurity is an important driver of cardiovascular disease risks.…”
Section: Discussionmentioning
confidence: 99%